Countering Radicalisation in UK: How to “Uplift” the Prevent Scheme - Quivooij, Romain (2017)
The recent attacks that struck Manchester and London have called attention to the alleged shortcomings of the Prevent scheme. Does the cost of the British counter-radicalisation strategy outweigh its benefits? Which new initiatives should be launched first?